CO2-recycling biomass gasification system for highly efficient and carbon-negative power generation. (15th November 2015) - Prabowo, Bayu; Aziz, Muhammad; Umeki, Kentaro; Susanto, Herri; Yan, Mi; Yoshikawa, Kunio
Graphical abstract: Highlights: A biomass gasification system with CO2 -recycling is proposed. Behavior and performance of the system are examined. Efficiency enhancement and emission reduction by CO2 -recycling. Highly pure CO2 stream in the exhaust gas. Potential implementation of a highly efficient and carbon-negative power system. Abstract: This study explored the feasibility of biomass CO2 gasification as an effective method for implementing the concept of a carbon-negative power system through bioenergy with carbon capturing and storage. A CO2 -recycling biomass gasification system was developed and examined using the thermal equilibrium model. Sensitivity analysis was performed by varying the gasifier temperature from 750 to 950 °C, and the turbine inlet temperature (TIT) and turbine exit temperature (TET) of the gas turbine from 1000 to 1200 °C and from 900 to 1000 °C, respectively. The gasifier efficiency was increased by an increase in the CO2 recycling ratio with the more significant trend shown at the lower gasifier temperature. The turbine efficiency decreased as the CO2 recycling ratio to the gasifier increased over a certain limit, a ratio of 0.55 in most cases. A pressure ratio of 2.3 was optimum in terms of turbine efficiency. Under the examined conditions, the optimum conditions for gaining the highest system efficiency, 39.03%, were a recycling ratio of 0.55 and a TET and TIT of 1000 and 1200 °C respectively. The proposed system had 7.57% higher efficiency and exhausted 299.15 g CO2 /kW h less CO2 emissions than conventional air gasification. Combined with carbon capturing and storage, the system potentially generates carbon-negative power generation with intensity of around 1.55-kg CO2 /kg wet-biomass and a maximum efficiency penalty of 6.89%.